The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1002/ar.22433
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Prior to Chondrocyte Cell Death During the Degeneration of Meckel's Cartilage

Abstract: The central portion of Meckel's cartilage degenerates almost immediately after birth. Whether autophagy is involved in this process remains unclear. Thus, to explore the role of autophagy during this process, we have detected the expression of autophagy and apoptosis-related markers in embryonic mice. In E15, Beclin1 and LC3 expressions were weak and negative in Meckel's cartilage, respectively. In E16, chondrocytes of the central portion became hypertrophic. Moderate immunoreactivities of Beclin1 and LC3 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 28 publications
1
21
0
2
Order By: Relevance
“…Recent studies have demonstrated that autophagy is involved in certain bone and cartilage diseases, such as cervical disc degeneration (42), cartilage degeneration of the temporomandibular joint (23), degradation of Meckel's cartilage (43) and OA (44). However, the results regarding changes in autophagy and the specific role of autophagy in the progression of OA are sometimes contradictory (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that autophagy is involved in certain bone and cartilage diseases, such as cervical disc degeneration (42), cartilage degeneration of the temporomandibular joint (23), degradation of Meckel's cartilage (43) and OA (44). However, the results regarding changes in autophagy and the specific role of autophagy in the progression of OA are sometimes contradictory (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…In surgically induced and age-related OA model, reduced autophagy and increase in apoptosis were observed [21]. Autophagy defect occured before chondrocyte cell death during Meckel cartilage degeneration [26]. Our present study also showed that knee joints from Vhl cKO mice with age-related and surgically induced OA displayed increased numbers of apoptotic chondrocytes and decreased expression of autophagy marker LC3II and Beclin1, suggesting a novel role of Vhl in maintaining cartilage homeostasis by regulating chondrocyte survival and autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…Despite that the chondrocytes in this portion become hypertrophic, they do not express chondrogenic differentiation markers, such as Col X and Ihh (Chung et al, 1995; this study), suggesting an arrest of chondrogenic differentiation prior to degeneration. Previous studies have implicated multiple factors and cellular processes in degeneration and resorption of Meckel’s cartilage, including several matrix metalloproteinases (Ishizeki and Nawa, 2000; Sakakura et al, 2007a, 2007b), macrophages (Harada and Ishezeki, 1998; Sakakura et al, 2005; Tsuzurahara et al, 2011), and possible autophagy and apoptosis (Trichilis and Wroblewski, 1997; Yang et al, 2012). However, the underlying mechanism that is responsible for the arrest of chondrogenic differentiation and subsequent degeneration of Meckel’s cartilage remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…However, unlike the fate of those mesoderm-derived cartilaginous elements and other CNC-derived cartilages such as cranial base, the majority of Meckel’s cartilage does not develop further and becomes degenerated. While previous studies have revealed potential contributions of several factors and cellular processes to the disappearance/resorption (Trichilis and Wroblewski, 1997; Harada and Ishizeki, 1998; Sakakura et al, 2005, 2007a, 2007b; Tsuzurahara et al, 2011; Yang et al, 2012), signaling pathways that prevent further differentiation and trigger degeneration of Meckel’s cartilage remain elusive.…”
Section: Introductionmentioning
confidence: 99%